Metodologias socioeducativas desenvolvidas pela rede de ação integrada para combater a escravidão no maranhão - RAICE - PEREIRA, Leidiane de Souza Silva (2022)
Brazil is currently experiencing a configuration of a re-signified, contemporary slave model that has left strong damages since colonization. Concerned with this reality, this work aims to analyze the socio-educational methodologies, specifically developed by the Integrated Action Network to Combat Slavery in Maranhão-RAICE, at the Carmen Bascarán Center for the Defense of Life and Human Rights. The RAICE project was born from the concern with the continuous and challenging problem of how society and the State can meet the demand of those interested for real changes in their living conditions. In this way, it develops socio-educational actions (classes, workshops, training and meetings) with the intention of offering social, political and human training to children and adolescents of workers rescued from slave labor. We used as methodology the qualitative approach with an epistemological focus on historical materialism that proposes the analysis of phenomena in a critical way; as research techniques were interviews and document analysis. The socio-educational methodologies are based in this study as practices that intervene in the social reality of the subjects considering the access to art and culture as a fundamental right of the human being, and in the perspective of the diffusion and valorization of the different expressions, manifestations knowledge and tradition that are part of the cultural identity of those involved. However, the criminal act of slave labor is the result of a model that reifies relationships, violates rights and steals the dignity and freedom of the individual. Therefore, Sakamoto (2006); Soares (2016); Freire (2019); Gohn (2011); Coast (2021); Gadotte (2011), are authors who supported the writing and theoretical reflections as well as the construction of the product of this dissertation elaborated in cultural circles through the fanzine methodology. We believe that through them we can contribute to the understanding and systematization of the socio-educational methodologies adopted by the team because, based on the conscious execution of these methodologies, this process can be useful for other institutions and other people who also work in the education of children and adolescents through the artistic, sporting and cultural activities.